THE ROLE OF THE ChILDREN IN THE EDUCATIONAL PROCCESS IN SCHOOL-FAMILY PARTNERSHIP - Olimova Nafisaxon Toxirjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. The educational process is a joint endeavour including schools, families, and children. Although much research emphasises the roles of parents and teachers, the child’s position in this collaboration is a vital yet frequently neglected component. This paper analyses the role of children in the educational process within the school-family partnership, emphasising their responsibility, participation, and engagement. It examines how children actively engage in their learning experiences and the methods by which schools and families can facilitate their autonomy. The study employs an analytical methodology, utilising previous research to examine the impact of children’s motivation, autonomy, and communication skills on academic achievement. The findings indicate that children significantly influence their educational experiences, and promoting their active involvement improves overall learning outcomes.